Esterification of oleic acid by heteropolyacid/TiO2SiO2 catalysts synthesized from less expensive precursors. Issue 3 (11th March 2015) - Sheikh, Rizwan; Shao, Godlisten N.; Khan, Zakir; Abbas, Nadir; Kim, Hee‐Taik; Park, Yeung‐Ho
Abstract A series of 12‐tungstophosphoric acid [HPW, H3PW12O40 (HPW)] catalysts supported on mesoporous titania–silica composite (TSC) were prepared by impregnation method. Primarily, TSC with mesostructure was successfully prepared by a modified sol–gel process using a less expensive silica precursor (sodium silicate) and titanium oxychloride as a titania source. In order to develop catalysts with various properties, the HPW loading over mesoporous TSC was controlled between 5 and 50 wt%. The surface morphology and structural properties of the prepared catalysts were characterized using N2 gas physisorption analysis, Fourier transform infrared spectroscopy, X‐ray diffraction, ultraviolet spectroscopy, transmission electron microscopy, and scanning electron microscopy analysis. The X‐ray diffraction and ultraviolet spectroscopy results were useful in determining the HPW dispersion on the support material. The catalytic activities of the samples were tested in liquid phase esterification of oleic acid with methanol. The results suggested that HPW dispersion on the support material was essential for the stability and performance of the catalysts during the esterification reaction. Even though the activity of the synthesized catalysts increased with increasing HPW loading, the homogeneity decreased in the samples with higher HPW content (30–50 wt%). The 20%HPW/TSC sample was found to be an active and catalytically stable catalyst, which was successfully regenerated and recycled for three consecutive runs. Copyright © 2015 Curtin University of Technology and John Wiley & Sons, Ltd.